The Degree to Which the Teachers Who Won the Queen Rania Al-Abdullah Award for Educational Excellence Possess and Practice Twenty-First Century Skills from their Point of View - Al-Salamat, Mohammed Musa; Al-Momeni, Jehad (Journal of Educational and Psychological Sciences, 2024)
The current study aimed to identify the degree of possession and practice of the teachers who won the Queen Rania Al-Abdullah Award for Educational Excellence for the skills of the twenty-first century from their point of view, The researcher followed the descriptive survey method, The study population consisted of (274) male and female teachers, while the study sample consisted of (162) male and female teachers who won the Queen Rania Al Abdullah Award for Educational Excellence in the Hashemite Kingdom of Jordan., and to achieve the objectives of the study, two tools were developed: a questionnaire to measure the degree of teachers' possession of twenty-first century skills, and it consisted of (25) items, and a questionnaire to measure the degree of teachers' practice of twenty-first century skills, and it consisted of (25) items It was applied to the study sample after verifying their validity and reliability, and the results showed that the degree of ownership and the degree of practice of the twenty-first century skills by the teachers who won the Queen Rania Al-Abdullah Award for Educational Excellence from their point of view was high, and the results showed that there were no statistically significant differences due to the variables (sex, qualification, specialization, years of experience) in teachers' possession and practice of twenty-first century skills the tool as a whole, and the presence of statistically significant differences due to the educational qualification variable in the field of learning skills and creativity.
Keywords: The degree of Possession; the Degree of Practice; the Skills of the Twenty-First Century; the Queen Rania Al-Abdullah Award for Educational Excellence